STUDY OF THE PATHOLOGY AND PARASITIC AFFECTION OF LIVER IN SHEEP AND CATTLE AT MOSUL AREA - I. Al-Sultan , I.; 0. Youkhana , S.; M. Maliran, O. (The Iraqi Journal of Veterinary Medicine, 1994)
A sample of (700) seven hundred out of (3000) three thousend randamly collected livers of sheep and cattle from Mosul abatteir during a biweekly visits of six months period, has been subjected to both gross and histopathological examinations. Results indicated that parasites induced the highest perecntages of tisse changes in the livers of cattle and sheep, the parasites responsible were hydatid cysts and Fasciola gigantica. gigantica. which indicated that Mosul and surrounding areas were endemic with these parasites. Typical cases of liver cirrhosis were rocognized in cattle and loss in sheep. Mixed infection of mentioned parasites with liver abcesses were also recognized in cattle and sheep. Liver abcesses and hepatic necrosis were diagnosed more frequently in sheep than in cattle. A diffuse form of lesions was found in cattle while the focal form was encounterd in sheep. Congestion and degenerative changes like fatty livers were not seen in cattle but formed a respective percentage (1%) and (1.1%) in sheep. Other conditions were identified like icteric livers their percentages were low and closely related in both species of animals.